Soybean meal+sorghum grain, alfalfa hay, and dehydrated alfalfa pellets as protein supplements for beef cows grazing dormant, tallgrass-prairie - DelCurto, T.; Cochran, R.C.; Corah, L.R.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty-six pregnant. Hereford x Angus cows were randomly assigned to one of three winter supplement treatments: 1) soybean meal+sorghum grain, 2) alfalfa hay, or 3) dehydrated alfalfa pellets. Cows supplemented with dehydrated alfalfa pellets gained more (P<.05) weight during gestation and lost the least (P<.05) weight at calving. However, no differences (P>.10) were detected in cow body condition change. reproductive efficiency, or calf growth.
Keywords: Beef; Soybean meal; Sorghum grain; Alfalfa hay; Dehydrated alfalfa pellets; Protein; Dormant, tallgrass-prairie